Elements of a Workplace Culture of Health, Perceived Organizational Support for Health, and Lifestyle Risk. Issue 7 (September 2018) - Payne, Julianne; Cluff, Laurie; Lang, Jason; Matson-Koffman, Dyann; Morgan-Lopez, Antonio
Purpose: We investigated the impact of elements of a workplace culture of health (COH) on employees' perceptions of employer support for health and lifestyle risk. Design: We used 2013 and 2015 survey data from the National Healthy Worksite Program, a Centers for Disease Control and Prevention (CDC)-led initiative to help workplaces implement health-promoting interventions. Setting: Forty-one employers completed the CDC Worksite Health Scorecard to document organizational changes. Participants: Eight hundred twenty-five employees provided data to evaluate changes in their health and attitudes. Measures: We defined elements of a COH as environmental, policy, and programmatic supports; leadership and coworker support; employee engagement (motivational interventions); and strategic communication. Outcomes included scores of employees' perceptions of employer support for health and lifestyle risk derived from self-reported physical activity, nutrition, and tobacco use. Analysis: We estimated effects using multilevel regression models. Results: At the employee level and across time, regression coefficients show positive associations between leadership support, coworker support, employee engagement, and perceived support for health ( P < .05). Coefficients suggest a marginally significant negative association between lifestyle risk and the presence of environmental and policy supports ( P < .10) and significant associations with leadership support in 2015 only ( P < .05). Conclusion: Relational elements of COH (leadership and coworker support) tend to be associated with perceived support for health, while workplace elements (environmental and policy supports) are more associated with lifestyle risk. Employers need to confront relational and workplace elements together to build a COH.